Digital innovation, institutional environment and air quality improvement - Ren, Hang; Huang, Jianzhong; Ren, Jinxin (Frontiers in Environmental Science, 2025)
The advancement of digital innovation has provided new perspectives for promoting green and sustainable development. This study examines data from 285 prefecture-level cities in China between 2015 and 2022 to systematically investigate the impact of digital innovation on air quality improvement, with a specific focus on the moderating role of institutional environment in the relationship between digital innovation and air quality enhancement. The findings reveal that the development of digital innovation has a significant positive effect on air quality improvement, a conclusion that remains robust after a series of robustness tests. Mechanism analysis indicates that digital innovation can improve air quality through channels such as optimizing industrial structure, increasing government expenditure on energy conservation and environmental protection, promoting green technology advancement, and facilitating the development of digital finance. Heterogeneity tests demonstrate that the air governance effect of digital innovation is more pronounced in central cities, large-scale cities, and cities with higher levels of education investment. Further analysis shows that the institutional environment can amplify the positive impact of digital innovation on air quality, particularly in regions with well-developed institutional environments, such as cities with sound market mechanisms, favorable financial innovation conditions, and high economic openness. Therefore, it is essential to strengthen the foundation of digital innovation and optimize the support of institutional environment to improve air quality.